Effect of folic acid supplementation on plasma total homocysteine levels and glycemic control in patients with type 2 diabetes: A systematic review and meta-analysis - Patcharaporn Sudchada (2018)
Aim: The evidences illustrating the effects of folic acid supplementation (FAS) in individuals with type 2 diabetes on plasma total homocysteine (tHcy) levels and glycemic control have been contradictory. The aim of the study was to systematically search and quantitatively analyze the effect of FAS on tHcy levels and HbA1c compared with placebo. Methods: We searched PubMed, Scopus, and Embase up to March 2012 without language restriction. Key words " folic acid" and " diabetes mellitus" with slight modifications based on the sources for search strategy were used. References of initially identified articles were examined to identify any other relevant studies. A random-effects model was used for estimation the pooled effect estimates (weighted mean different, WMD). Results: Of 6185 studies identified, 4 studies with 183 patients were included. FAS had statistically significant effect on tHcy levels [WMD, -3.52; 95% confidence interval (CI), -4.44 to -2.60]. However, the effect on HbA1c levels [WMD, -0.37; 95% CI, -1.10 to 0.35] was not significant. Conclusions: Folic acid supplementation in patient with type 2 diabetes mellitus may reduce tHcy levels and have a trend to associate with better glycemic control compared with placebo. Further longitudinal studies on these intervention and outcomes are warranted. © 2012 Elsevier Ireland Ltd.